Reforma regulatória no contexto brasileiro - Coelho, Carina Cavalcante (2011)
This study aimed to analyse the potencial and obstacles of the adoption of the Regulatory Impact Analysis and the oversight body in the Brazilian context. For this, we carried out a field research with representatives of institutions involved with AIR, such as regulatory agencies and Civil House, as well as experts with publications on the top. Twelve semi-structured interviews were conducted around questions compiled from the previously explored in the theoretical knowledge of the work. It was concluded that from an environment of concern for regulatory quality in Brazil, both the central administration and regulatory bodies investigated have undertaken efforts to achieve a more effective regulatory system. However, there is a long way to go and many hurdles to overcome. Concerning the RIA and the oversight body, the strength, technical expertise, institutional design are some of the obstacles that must be overcome to reach the Brazil actually an improvement of regulatory quality.